PENGARUH KUALITAS PRODUK DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Pada Pengguna Smartphone Samsung di FEB Universitas Islam Malang) - Rudy Cahyo Widodo; N. Rachma (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT The purpose of this study was to determine the direct effect of product quality variables, brand image on satisfaction. Product quality, brand image, satisfaction with loyalty. And also the indirect influence of product quality, brand image on loyalty through satisfaction with Samsung smartphone users. The research method used is quantitative. The population and sample used in this study were students of the Faculty of Economics and Business, Malang Islamic University. The sampling technique uses accidental sampling technique, while hypothesis testing uses path analysis. The results of this study provide empirical evidence that there is a direct effect of product quality, brand image on satisfaction. Product quality, brand image, satisfaction with loyalty. There is also an indirect influence on product quality and brand image on loyalty through satisfaction. Keywords: Product Quality, Brand Image, Satisfaction, Loyalty.